The Effect of Capital Requirement Regulation on the Transmission of Monetary Policy: Evidence from Austria - Philipp Engler; Terhi Jokipii; Pablo Rovira Kaltwasser; Christian Merkl; Lúcio Vinhas de Souza (Oesterreichische Nationalbank (OeNB), 2005)
This paper analyzes the role of bank capitalization on the transmission of monetary policy, using a quarterly dataset for Austrian banks spanning from 1997 to 2003. A substantial understanding of the transmission mechanism in different countries of the euro zone is not only of academic interest, but also an important prerequisite for central bankers to effectively accomplish their monetary policy goals. While we do find evidence in favor of the bank lending channel, with an important role active for capitalization, we are unable to confirm whether the bank capital channel is in force in Austria. Our results indicate some counter-cyclicality in lending activity, a finding that is in line with the existing Austrian literature.
Keywords: E4; E5; 330; Transmission of monetary policy; Bank capital regulation; Austria